2015
DOI: 10.14738/abr.32.1009
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Deposit Money Banks on the Growth of the Agricultural Sector in Nigeria

Abstract: The*objective*of*this*study*was*to*investigate*the*role*of*deposit*money*banks* credit* on* the* growth* of* the* agricultural* sector* in* Nigeria* between* the* periods* 1988* to* 2011.* An* exVpost* facto* research* design* was* used* for* the* study.* Three* research* objectives* were* formulated.* Data* were* sourced* principally* from* the* secondary*sources*and*was*collected*from*the*CBN*Statistical*Bulletin.*The*Data* were* analyzed* using* the* ordinary* least* square* multiple* Regression* Statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This will help to boost economic activities within the country because lack of capital retards investment. Anthony, Gabriel, and Arikpo (2015) investigate the effect of deposit money banks credit on the growth of the agricultural sector in Nigeria between the periods 1988 to 2011. They used the ordinary least squares method of multiple regression to analyze the data.…”
Section: Empirical Literaturementioning
confidence: 99%
“…This will help to boost economic activities within the country because lack of capital retards investment. Anthony, Gabriel, and Arikpo (2015) investigate the effect of deposit money banks credit on the growth of the agricultural sector in Nigeria between the periods 1988 to 2011. They used the ordinary least squares method of multiple regression to analyze the data.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Moreover, Innumerable policies have been made accessible to provide agricultural finance assigned to commercial banks to provide to loans and advanced to farmers. Nevertheless, the part has not been able to grab as a result of higher interest rates charge with conditions of collateral (Anthony et al, 2015). The assessment of commercial bank in the area of loans and advances can be measured via monetary policy tools and market intervention portfolio (Jegede, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The level of economic development of an economy is influenced by a number of elements, including the endowment of natural resources, technical know-how, the supply of trained labor, and, of course, capital resources (Ogege and Shiro, 2013). The functions performed by deposit money banks are encouragement of savings, provision of capital needed for development, encouragement of trading activities through the use of cheques, encouragement of investment, provision of managerial advice to industrialists who do not engage the services of specialists and rendering financial advice (Ogar, Gabriel and Arikpo, 2015). Results from earlier studies showed that the topic under study had a variety of results.…”
Section: Introductionmentioning
confidence: 99%